Root Length Changes in Orthodontically Displaced Teeth Treated with the Corticotomy Approach - Irinel Panainte; Irina Zetu; Cristina Molnar; Constantin Budescu-Stanica; Ela Oprea; Mariana Pacurar (European Scientific Journal, ESJ, 2022)
The aim of the study: Corticotomy-facilitated orthodontics is a modern approach to resolve complicated orthodontic cases that may increase the pace of tooth movement. The study's goal was to assess the changes that occurred at the root level following orthodontic treatment when corticotomy was used. Material and methods: Based on Cone Beam Computer Tomography, measurements of the root length at T0 (before corticotomy) and T1 (after corticotomy) were taken after splitting the individuals into two groups (maxillary and mandibular corticotomy) (6 months after surgery). For statistical analysis of the data, many tests were utilized. Results: The root length values obtained at T1 showed minimal changes in length, with statistically insignificant values (for the maxillary arch, the values obtained were 13.36 ± 2.41 mm for women and 14.26 ± 2.06 mm for men; for the lower arch, the measured values were 12.38 ± 2.09 mm for women and 11.56 ± 2.29 mm for men). The canine on the left hemiarcade had the most significant change in root length following treatment, with a value assessed at T1 of 16.72 ± 1.78 mm, which was statistically significant, p 0.05. Conclusion: According to the data obtained in this study, when orthodontic therapy is associated with corticotomy, there is a decrease in root resorption that may occur in the case of conventional orthodontic treatments.